COVID-19 and Systemic Lupus Erythematosus: Focus on Immune Response and Therapeutics - Spihlman, Allison P.; Gadi, Nirupa; Wu, Samantha C.; Moulton, Vaishali R. (Frontiers in Immunology, 2020)
The SARS-CoV-2 novel coronavirus has caused the COVID-19 pandemic with over 17 million cases and over 666,000 deaths worldwide as of late July 2020. The populations most affected are the elderly and especially those with underlying comorbidities. In terms of race and ethnicity, black and hispanic populations are affected at disproportionately higher rates. Individuals with underlying conditions that cause an immune-compromised state are considered vulnerable to this infection. The immune response is an important determinant in infections including coronaviruses, not only in the antiviral defense but also in the disease progression, severity and clinical outcomes of COVID-19. Systemic lupus erythematosus is a chronic autoimmune disease which also disproportionately afflicts black and hispanic populations. In lupus patients, an aberrant immune response is characterized by the presence of circulating autoantibodies, lymphopenia, aberrant T cells and proinflammatory cytokines along with defective regulatory mechanisms, leading to immune-mediated damage to tissues. Lupus patients are often treated with immune-suppressants and therefore are immune-compromised and more susceptible to infections and maybe vulnerable to coronavirus infection. While the anti-viral immune response is important to protect from coronavirus infection, an uncontrolled proinflammatory cytokine response can lead to cytokine storm which causes damage to the lungs and can lead to significant morbidity and mortality. Better understanding of the underlying immune response and therapeutic strategies in lupus and COVID-19 is important to guide management of this deadly infectious disease in the context of lupus and vice-versa.